Muscular system (Atlanta : Benjamin/Cummings, 2000)
Presents topics related to muscles at gross and cellular levels to demonstrate the structure and function of the muscular system, using detailed graphics, animation, sound, video, and interactive quizzes
System requirements: Windows: 166 MHz Intel Pentium processor or greater Windows 95/98/NT4/2000, monitor capable of displaying 800 x 600 pixels, 32 MB or more of installed RAM, quad-speed CD-ROM; Macintosh: 120 MHz PowerPC, MAC OS 8.1 or later, monitor capable of displaying 800 x 600 pixels, 18 MB or more of available RAM, quad-speed CD-ROM
Keywords: Muscles; Muscle cells